Discuss about Foucault’s Method: Interpretative Strategies of Verbal and Visial - E. N. Ishchenko (Концепт: философия, религия, культура, 2020)
The problem with M. Foucault’s method, foundations and limits of applicability is one of the central issues in the discussions of his many followers. Reconstruction of the method, per se, involves various strategies for working with his texts. The article proposes a comparative analysis between the interpretations of R. Descartes’s philosophical ideas and Manet’s artistic paintings in the works of M. Foucault. Such an approach through a collision of analysis of visual and verbal objects allows us to identify the general contours of Fucoldian methodology. Interpreting Cartesian ideas, M. Foucault actively uses the metaphors of light and darkness and refers to the possibilities of verbalized visibility. R. Descartes’s ideas turned into a basis for switching to a new register of attitudes towards madness in European culture. In turn, the interpretation of E. Manet’s paintings, proposed by M. Foucault, is based on an analysis of the revolutionary changes in the understanding of art introduced by an outstanding French artist. It affects not only the aesthetic context itself, but leads to new relations between a painting and an audience and also helps to establish new sociocultural practices. Foucault’s verbalization of visual is radically different from approaches of traditional art history. Thus, in Foucault’s work, verbal and visual are closely intertwined with each other and his method can be successfully applied when working with verbal and visual objects.